2014
DOI: 10.17795/jhealthscope-17795
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Nitrate Reduction by Electrocoagulation Using Response Surface Methodology

Abstract: Background:The presence of nitrate and its intermediates are considered undesirable compounds in the environment. Various methods have been proposed to remove nitrate from wastewater and water streams. Objectives: In this study, we investigated removal of nitrate from an aqueous solution by the process of electrocoagulation, using aluminum/graphite as the anode/cathode electrodes. Materials and Methods:We applied response surface methodology (RSM) as the statistical method for modeling, and optimizing the appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The obtained results indicated that the EC-EO method reduced the nitrate concentration by 90% within 90 minutes at a current value of 0.6 ampere. Hossini and Rezaee (2014) combined an EC cell, which supplied with two aluminium anodes and two graphite cathodes, with an air stripping system to remediate nitrate from wastewater. The obtained results demonstrated that this combined system was efficient to remove as high as 97% of nitrate within 120 minutes of electrolysing at a current of 0.14 ampere.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results indicated that the EC-EO method reduced the nitrate concentration by 90% within 90 minutes at a current value of 0.6 ampere. Hossini and Rezaee (2014) combined an EC cell, which supplied with two aluminium anodes and two graphite cathodes, with an air stripping system to remediate nitrate from wastewater. The obtained results demonstrated that this combined system was efficient to remove as high as 97% of nitrate within 120 minutes of electrolysing at a current of 0.14 ampere.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Akhondi et al conducted a study on the removal of cadmium by the EC method and demonstrated that the maximum removal efficiency of cadmium was at 185 W, operation time of 40 min, and pH of 10.25 (31). In another study the maximum removal efficiency of nitrate from drinking water was 84% at 25 V using Hossini and Rezaee indicated that by applying the electric current of 0.14 A for 120 min, the nitrate content decreased to 97% (32). Furthermore, Adhoum et al showed that the optimum current for the maximum removal of phenolic compounds from wastewater was at 75 mA/Cm 2 (33).…”
Section: Effect Of Voltage On Nitrate Removal Using the Electrocoagulmentioning
confidence: 99%
“…EC uses a direct electrical current source between metal electrodes that are partially immersed in the electrolyte. Electric current causes the metal plates to be dissolved in the wastewater (17,18). Two widely used metals in electrocoagulation process are iron and aluminum (11).…”
Section: Introductionmentioning
confidence: 99%